2022
DOI: 10.1007/s13187-021-02123-x
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy Correlates to HPV Vaccination Among US Adults Ages 27–45

Abstract: Human papillomavirus (HPV) vaccination is now available for adults aged 27–45 as a shared clinical decision. Health literacy skills (i.e., accessing, understanding, appraising, applying information) may facilitate vaccine decision-making for adults with a provider recommendation. This study assessed associations between health literacy skills and willingness to get a provider-recommended HPV vaccine among newly eligible US adults. In 2020, US participants (51% women), aged 27–45 years, were surveyed online ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Previous studies that surveyed adults aged 27 to 45 years after the ACIP recommendation update found that the majority of these adults were likely to ask health care professionals about HPV vaccination and willing to get a vaccine if recommended by their clinician . The likelihood of receiving the HPV vaccine was highly associated with the perceived likelihood of benefiting from the vaccine .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies that surveyed adults aged 27 to 45 years after the ACIP recommendation update found that the majority of these adults were likely to ask health care professionals about HPV vaccination and willing to get a vaccine if recommended by their clinician . The likelihood of receiving the HPV vaccine was highly associated with the perceived likelihood of benefiting from the vaccine .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies that surveyed adults aged 27 to 45 years after the ACIP recommendation update found that the majority of these adults were likely to ask health care professionals about HPV vaccination and willing to get a vaccine if recommended by their clinician. 29,30 The likelihood of receiving the HPV vaccine was highly associated with the perceived likelihood of benefiting from the vaccine. 29 Similarly, according to a study that surveyed primary care physicians, the majority of physicians reported that they would be more likely to recommend HPV vaccination to adults aged 27 to 45 years due to the new ACIP recommendation.…”
Section: Discussionmentioning
confidence: 99%
“…This research has identified low awareness of eligibility for HPV vaccination ( Alber et al, 2021 ), low knowledge of HPV-related cancers that directly affect men ( Thompson et al, 2020 ), concerns about HPV vaccine safety, and beliefs that the HPV vaccine is unnecessary ( Muthukrishnan et al, 2022 ) among mid-adults, which may pose barriers to uptake. Mid-adults’ willingness to be vaccinated has been identified as being positively associated with level of knowledge about HPV vaccination, perceived ease of understanding HPV vaccine information, and perceived vulnerability to HPV-related cancers ( Galvin et al, 2023 ). Positive attitudes toward HPV vaccination, perceived effectiveness of vaccines against HPV infection, and perceived likelihood of benefiting from HPV vaccination have been reported to increase mid-adults’ perceived likelihood of getting vaccinated ( Thompson et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Improving cervical cancer health literacy levels is one of the keys to preventing cervical cancer [12]. Several studies have shown that an increased level of cervical cancer health literacy is associated with improved HPV vaccination, cervical cancer screening, and treatment [13][14][15]. In China, the HPV vaccine is not included in the national immunization program, but a cervical cancer screening program was instituted in 2009 as part of primary health care inviting rural women aged 35-64 years to undergo regular screenings.…”
Section: Introductionmentioning
confidence: 99%